Juvenility, maturation and rejuvenation in plants: adventitious bud formation as a novel rejuvenation process. Issue 1 (2nd January 2019) - Heide, Ola M.
ABSTRACT: Juvenility and maturation in plants are briefly reviewed with emphasis on the regulation of phase change and rejuvenation. The invariable rejuvenation of offspring by the process of sexual reproduction is highlighted and the processes and control mechanisms of zygotic and somatic embryogenesis are compared and discussed. It is concluded that the two phenomena share a range of genetic, hormonal and environmental control mechanisms. Central in this connection are temporal changes in the expression and abundance of miRNA156 and miRNA172 and their respective SPL and AP transcription factors, which regulate both phase change and embryogenesis. The important regulatory role of SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASES and the hormonal action of strigolactones in somatic embryogenesis are also discussed. Furthermore, the paper cites a number of examples of complete rejuvenation brought about by adventitious bud (shoot) formation in both herbaceous and woody species, identifying this as a novel cellular pathway of rejuvenation in plants. Similarities and distinctions between somatic embryogenesis and adventitious shoot formation are discussed. Supported by emerging molecular evidence, it is suggested, that for the act of rejuvenation, the adventitious bud formation process utilises essential parts of the plants' intrinsic zygotic embryogenesis development program.